Educational Opportunities and the Role of Institutions - Andreas Ammermüller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Educational opportunities determine the intergenerational mobility of human capital and are affected by institutional features of schooling systems. The aim of this paper is twofold. It intends to show how strongly student performance depends on student background at two important stages in a student?s life as well as to explain cross-country differences in educational opportunities by schooling institutions. A difference-in-differences estimation approach is applied to control for country-specific effects. The results imply that educational opportunities decrease with student age in most countries. However, the attitude of parents seems to become more important while the impact of social origin decreases. A greater differentiation of the schooling system as indicated by streaming and private schools is associated with a greater effect of social background while more instruction time limits the impact of social origin on student performance. Higher school autonomy increases the impact of parental influence.
Keywords: I21; J62; 330; Equality of educational opportunity; student performance; institutions; PISA; PIRLS; Bildungschancen; Bildungswesen; Bildungsniveau; Schätzung; Welt